THE INFLUENCE OF MARKETING MIX ON CONSUMERS PSYCHOLOGICAL FACTORS AND ITS IMPACT ON PURCHASING BEHAVIOR (SURVEY ON CONSUMERS OF DEVELOPER PT KENDALI PUTRA SURABAYA) - Marhadyta, Ajrina Valentine; Hamid, Djamhur; Suyadi, Imam (FIA UB, 2013)
Marketing mix is one of several types of strategies in marketing that is useful to find out which suitable strategies should be used in the company at the market. Elements of marketing mix nowadays have developed approaches starting from 4P, 5P, 6P, 7P and 15P. Besides, many companies in the world always improve their marketing concept if they want to be survivor and be the winner in the market as well as to get consumers’ value. It is very important for companies to survive in its business. The marketing concept has three main elements, which are consumers’ oriented, integrated marketing and consumers’ satisfaction. This study used the characteristics of consumers for doing a research at the developer since the marketing concept is believed to be the main key to achieve the goal of an organization in creating, delivering and communicating consumers’ value towards the selected market of the target. The approach is 4P in psychological factors toward purchasing behavior of consumers. Keywords: Marketing Mix, Psychological factors, and Purchasing Behavior of Consumers.